Hilirisasi Buah Naga Melalui Pemberdayaan Petani di Era Revolusi Industri 4.0 - Hartono, Rudi; Hutasuhut, Ida Juliana; Endar Purnawan; Dodot Sudiyanto; Wanto; Neli, Neli; Nashirun; Nilhakim, Nilhakim (Jurnal Pengabdian Kepada Masyarakat, 2025)
Dragon fruit downstreaming through farmer empowerment is one of the important strategies in increasing added value and competitiveness of agricultural products in the era of the Industrial Revolution 4.0. This research aims to identify challenges and opportunities in the downstream process of dragon fruit through farmer empowerment by utilizing digital technology. This approach emphasizes the use of smart technologies such as the Internet of Things (IoT), big data, and automation to improve production efficiency, distribution, and market access for dragon fruit farmers. Through digitally integrated supply chain optimization, it is expected that farmers can be more empowered in managing crops, improving product quality, and expanding access to local and international markets. The results showed that with technological innovation, farmers have great potential to increase productivity and competitiveness of dragon fruit products in the global market. However, the implementation of this technology also faces challenges, especially in terms of farmers' digital literacy and technological infrastructure. Therefore, collaboration between the government, academia, and the private sector is needed to provide assistance and training to farmers in order to optimize the use of technology in the agricultural sector